Optimization of operating conditions of a cooling tunnel for production of hard candies - Reinheimer, Maria Agustina (2012)
On large industrial scales, the cooling stage in the production process of hard candies is one of the most critical unit operations because many quality problems such as deformation, fragility and aggregation may appear in this stage. Therefore, the optimization of the operating conditions of the cooling tunnel plays an essential role from a quality point of view. The objective of this work is to develop a mathematical model to determine the optimal operating conditions of the cooling tunnel in order to assure the product quality. The resulting PDAEs were converted to a set of nonlinear algebraic equations using the centered finite difference approximation (CFDM) and were implemented into the optimization environment GAMS (General Algebraic Modeling System). Thus, the temperature profiles in the center and surface of the candy, air cooling temperature and velocity are simultaneously optimized. Three objectives functions based on the product quality are proposed. A sensitive analysis on the main model parameters was also made. The obtained results are discussed in detail. It is concluded that the developed model can be used as a useful tool to improve its operating efficiency and even to design a new cooling tunnel.